2016
DOI: 10.1016/j.psychres.2016.02.015
|View full text |Cite
|
Sign up to set email alerts
|

Equal access for all? Access to medical information for European psychiatric trainees

Abstract: Access to medical information is important as lifelong scientific learning is in close relation with a better career satisfaction in psychiatry. This survey aimed to investigate how medical information sources are being used among members of the European Federation of Psychiatric Trainees. Eighty-three psychiatric trainees completed our questionnaire. A significant variation was found, and information availability levels were associated with training duration and average income. The most available sources were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 9 publications
(7 reference statements)
1
11
0
2
Order By: Relevance
“…Previous findings suggest that websites and senior colleagues are amongst the preferred sources. 14 Practical structured peer review training courses endorse the concept of core competencies to peer review. 15 Such sets of universally agreed reviewer competencies, with some variation at the individual level, could provide the basis for both a training framework and ongoing evaluation of reviewer's quality.…”
Section: Discussionmentioning
confidence: 99%
“…Previous findings suggest that websites and senior colleagues are amongst the preferred sources. 14 Practical structured peer review training courses endorse the concept of core competencies to peer review. 15 Such sets of universally agreed reviewer competencies, with some variation at the individual level, could provide the basis for both a training framework and ongoing evaluation of reviewer's quality.…”
Section: Discussionmentioning
confidence: 99%
“…Participants value interacting with experts, as well as with their peers, believing this fosters reflective practice [5]. A survey of psychiatry trainees from 32 European countries showed that access to affordable medical information is relevant, particularly via the internet [6]. For instance, the European Federation of Psychiatric trainees is promoting online courses and summer schools [7], and provides online training material (e.g., psychotherapy guidebooks) [8].…”
Section: Online Cbt Could Be a Good Solutionmentioning
confidence: 99%
“…Both practitioner and guideline characteristics have been found to vary across European countries. With regard to the first, differences in duration, content and specialisation pathways of training provided in clinical psychology or psychiatry exist between countries [29][30][31]. Similarly, guidelines are available and perceived as beneficial to different extents across Europe, according to a qualitative study conducted by Gatej et al [1].…”
Section: Introductionmentioning
confidence: 99%